Chinese researchers' perceptions and use of open access journals: Results of an online questionnaire survey. Issue 3 (2nd March 2020) - Xu, Jie; He, Chen; Su, Jing; Zeng, Yuanxiang; Wang, Zixian; Fang, Fei; Tang, Wenhui
Abstract : This paper reports the results of a survey on Chinese researchers' perceptions and use of open access journals (OAJs). A total of 381 Chinese researchers from different universities and disciplines were investigated through an online questionnaire survey in August and September 2018. The results showed that most Chinese researchers are familiar with and have positive attitude to OAJs. They know OAJs mainly through their peers, colleagues, and friends. PubMed Central, PLoS, and COAJ (China Open Access Journals) are the most well‐known OAJ websites among Chinese researchers. As for use, most of the respondents read and cite OAJs frequently and have experience of publishing in OAJs. However, they strongly prefer to use OAJs indexed in reputable databases (e.g. Web of Science, WoS) when making publishing decisions. Significant differences can be seen among disciplines, with researchers in HSS areas using OAJs less frequently than researchers from other disciplines, although they have the same positive attitudes and are equally well informed about them. Younger researchers preferred to rely on prestigious institutions and authors when using OAJs.